2012
DOI: 10.1080/09658211.2012.667813
|View full text |Cite
|
Sign up to set email alerts
|

Acts of generating and their sources: Predicting the effects of imagery encoding on false recognition errors

Abstract: In the two experiments reported here the basis of the beneficial effects of generating images on false recognition errors is investigated. Acts of generating (descriptions, images, or both) were manipulated while examining the effects of the source of descriptions guiding imagery generations (participant vs peer). False recognition errors were relatively high across encoding conditions except when imagery generations were based on participants' own descriptions (Experiments 1 and 2). These differences in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Consistent with this possibility are studies showing that participants falsely report seeing objects appropriate to, but not actually embedded in, complex visual scenes (Brewer & Treyens, 1981;Malmstrom & LaVoie, 2002). To investigate imagery processing effects more directly, Foley et al (2012) asked some participants to visualize DRM scene descriptions. Results suggested that the act of deliberately creating images of self-generated descriptions greatly reduced falserecognition errors (.18;Foley et al, 2012, Experiment 2).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Consistent with this possibility are studies showing that participants falsely report seeing objects appropriate to, but not actually embedded in, complex visual scenes (Brewer & Treyens, 1981;Malmstrom & LaVoie, 2002). To investigate imagery processing effects more directly, Foley et al (2012) asked some participants to visualize DRM scene descriptions. Results suggested that the act of deliberately creating images of self-generated descriptions greatly reduced falserecognition errors (.18;Foley et al, 2012, Experiment 2).…”
mentioning
confidence: 80%
“…We manipulated imagery instructions to extend the work of Foley et al (2012Foley et al ( , 2009Foley et al ( , 2006 to autobiographical elaboration of DRM materials. We investigated the lure activation process by providing guided imagery instructions to some participants while others comprised a spontaneous imagery condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test construction was based on procedures used by researchers investigating the effects of pictorial (e.g., Israel & Schacter, 1997) and imagery (e.g., Foley et al, 2012; encoding on false memory rates. The 64-item memory test consisted of four kinds of test items: (a) 30 of the words presented during encoding were selected, three from each of the 10 presented lists, referred to here as presented instances; (b) 10 nonpresented This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was possible to code participants' spontaneous responses to each item and to examine the potential relationship between these responses and memory accuracy. In these studies involving the modified procedure, there was compelling evidence for the activation of spontaneous, self-referential activations about prior personal experiences (e.g., Foley et al, 2014;Foley et al, 2012). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Direct Assessment and Descriptions Of The Phenomenological Qmentioning
confidence: 99%